Pengaruh Teknologi, Pengadopsian Ukuran-Ukuran Kinerja Keuangan Dan Non Keuangan Terhadap Kinerja Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Dikawasan Industri Batam) - Yul Emri Yulis (Fakultas Ekonomi Universitas Pasir Pengaraian, 2018)
The purpose of this study is to test empirically the influence of technology, and the adoption measures of financial an non-financial performance measures to company performance. This research was conducted on Batam industrial area. The variables studied are technologies measured by instruments developed by withey et al (1983) with the dimensions of task variability and problem analyzability, and the adoption measures of proxy performance measures of financial and non-financial measures (Spencer et al, 2009), the two variables are independent variables, the dependent variable is company performance which is measured by profitability ratio. The data used are consist of primary data and secondary data. Secondary data in the form of financial data and primary data collected by using questionnaire. Research respondents are production managers and financial manager. Analysis method by using path analysis. The result of this study indicated that the technology has a positive and significant impact on the adoption measures of financial and non-financial performance, the adoption measures of financial performance and non-financial performance has a positive and significant impact on the company performance, technology has a positive and significant impact on company performance, the company’s performance indirectly has positive and significant impact on the adoption measures of financial and non-financial performance measures